Effect of norbixin-based poly(hydroxybutyrate) membranes on the tendon repair process after tenotomy in rats - Nascimento,Lízia Daniela e Silva (2019)
Abstract Purpose: To determine the efficacy of norbixin-based poly(hydroxybutyrate) (PHB) membranes for Achilles tendon repair. Methods: Thirty rats were submitted to total tenotomy surgery of the right Achilles tendon and divided into two groups (control and membrane; n = 15 each), which were further subdivided into three subgroups (days 7, 14, and 21; n = 5 each). Samples were analyzed histologically. Results: Histological analysis showed a significant reduction in inflammatory infiltrates on days 7, 14 (p < 0.0001 for both), and 21 (p = 0.0004) in the membrane group compared to that in the control group. There was also a significant decrease in the number of fibroblasts in the control group on days 7, 14 (p < 0.0001), and 21 (p = 0.0032). Further, an increase in type I collagen deposition was observed in the membrane group compared to that in the control group on days 7 (p = 0.0133) and 14 (p = 0.0107). Conclusion: Treatment with norbixin-based PHB membranes reduces the inflammatory response, increases fibroblast proliferation, and improves collagen production in the tendon repair region, especially between days 7 and 14.